Positive Emotions, Autonomy Support and Academic Performance of University Students: The Mediating Role of Academic Engagement and Self-Efficacy [Emociones Positivas, Apoyo a la Autonomía y Rendimiento de Estudiantes Universitarios: El Papel Mediador del Compromiso Académico y la Autoeficacia] - Oriol-Granado, X (Escuela Universitaria de Magisterio, 2017)
The overall objective of this study is to check if some variables such as autonomy support and positive affect experienced in the classroom are predictors of academic performance through self-efficacy and engagement in university students. The tested model confirm the expected results but notes that the self-efficacy does not shown a significant direct effect on performance. Therefore, a second model is tested. We include self-efficacy as a predictor of academic engagement eliminating direct effect of this variable on performance. The results show a greater adjustment in the second model, so that (1) positive emotions and autonomy support predict academic performance, self-efficacy and academic engagement (2) self-efficacy predicts higher levels of academic engagement and this variable improves academic performance (3) indirect effects also show that there are a mediation of these variables on the predictive relationship of autonomy support and positive emotions on performance. © 2017, Escuela Universitaria de Magisterio. All right reserved.